Pengaruh Penggunaan Berbagai Jenis Ikan sebagai Inang terhadap Kelangsungan Hidup Glochidia Kijing Taiwan (Anodonta woodiana Lea) - Hamidah, Afreni (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2006)
The research about the glochidia Anodonta woodiana Lea viability on host fishes has been conducted in the Laboratory of Zoology Biology Department Mathematic and Science Faculty Sriwijaya University from July – November 2004. The research applied completely randomized design with 5 treatments of host fish (Cyprinus carpio, Pristolepis fasciatus, Oreochromis niloticus, Trichogaster pectoralis and Clarias gariepinus) with 6 replications. The results of the research showed that the use of fishes host has influenced the glochidia viability. The highest glochidia viability was in Trichogaster pectoralis there was a great diffoence compared to other host fish. This result showed that Trichogaster pectoralis was the most effective host fish of Anodonta woodiana glochidia.